2021
DOI: 10.3390/antiox10040519
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide Supplementation Improves Oocyte Quality and Offspring Development by Modulating Mitochondrial Function in an Aged Caenorhabditis elegans Model

Abstract: Aging is associated with a decline in the quality of biological functions. Among the aging processes, reproductive aging is a critical process because of its intergenerational effects. However, the mechanisms underlying reproductive aging remain largely unknown. Female reproductive aging is the primary reason for limited fertility in mammals. Therefore, we attempted to investigate a modulator that can control female reproductive aging using a Caenorhabditis elegans model. In the present study, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 70 publications
(56 reference statements)
1
23
0
Order By: Relevance
“…It has been suggested that immunity and antioxidant defense, which regulate ROS production in response to bacterial colonization during intestinal aging, are major effectors of aging and lifespan in C. elegans [ 43 , 44 ]. Given that caffeine intake suppresses bacterial colonization of the intestine in aging animals ( Figure 1 D), we measured mitochondrial ROS levels using CellROX Green, which is a fluorogenic probe for measuring mitochondrial ROS in live cells [ 38 ]. We observed that the fluorescence intensity decreased significantly in the long-term caffeine-ingested wild-type animals ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that immunity and antioxidant defense, which regulate ROS production in response to bacterial colonization during intestinal aging, are major effectors of aging and lifespan in C. elegans [ 43 , 44 ]. Given that caffeine intake suppresses bacterial colonization of the intestine in aging animals ( Figure 1 D), we measured mitochondrial ROS levels using CellROX Green, which is a fluorogenic probe for measuring mitochondrial ROS in live cells [ 38 ]. We observed that the fluorescence intensity decreased significantly in the long-term caffeine-ingested wild-type animals ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the effect of caffeine intake on the mitochondrial ROS, CellROX ® Green (Invitrogen, Carlsbad, CA, USA) staining was performed as described previously [ 4 , 38 ]. Briefly, CellROX ® Green was freshly prepared as 5 mM stock solutions and diluted in the M9 buffer at a 1:500 dilution before treatment.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations